The Effect of The Implementation of Project-Based Learning Model in Improving The Learning Outcomes Of Students in Islamic Religious Education Subjects at Islamic Vocational High School of Pharmacy in Sumbawa - Muhammad Parhun; Nurkamariah; Wahyuddin (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2025)
The results of the researcher's observations with the class teacher who teaches Islamic Religious Education for class XII showed that Islamic Religious Education learning at the vocational school had not met the expected KKM. Also, many students felt bored with the learning model applied by the Islamic Religious Education subject teacher. In this study, the researcher used a project-based learning model. This study aims to determine whether there is an influence of the project-based learning model on the learning outcomes of Islamic Religious Education students. This research was conducted at SMK Islam Farmasi Sumbawa. This type of research uses a quantitative approach. The population of this study were students of SMK Islam Farmasi Sumbawa and the sample of this study was 38 students in class XII. This study used purposive sampling. Data collection techniques using observation, documentation, and questionnaires.